Mangroves as a nature-based solution for water and climate change issues in Macao: from scientific research to environmental education - Tagulao, Karen (Fostering applied research on the synergies between biodiversity and climate, 2022)
Publisher: Deutschland / Bundesamt für Naturschutz

Nature-Based Solutions for Environmental Education in the East Asian Context - Tagulao, Karen Araño (Enhancing Environmental Education Through Nature-Based Solutions, 2022)
Environmental education (EE) has long been practiced worldwide, while Nature-based solutions (NBS) is a relatively new concept. This chapter aims to provide an overview of the EE and NBS practices in East Asia and evaluate how these two valuable applications can be used concurrently. East Asia has a well developed environmental education (EE) programs and activities, both in formal and informal education. These ranges from developing green schools and campuses to establishing policies and acts. While EE has been actively practiced for decades in the region, the adoption of NBS to address environmental and societal challenges is limited. The educational benefits and opportunities from NBS are also lacking. Although there are some projects that can be classified as NBS, like the use of wetlands for wastewater treatment, they are not clearly categorized as one. These projects are also not integrated into environmental education programs. Considering this, the region should develop innovative environmental education programs for schools, universities and communities, that integrate NBS projects. Integrating the two together will boost the effectiveness of environmental education in raising environmental awareness and changing the environmental attitude and behavior of people, which will also help address societal issues.
Keywords: Environmental awareness; Environmental policies/acts; Green schools; Green universities; Sponge cities; Wetlands

Neuroendocrinology of Social Behavior in Teleost Fish - Gonçalves, David; Félix, Ana S.; Oliveira, Rui F. (Hormones, Brain and Behavior, 2017)

Development of Structure and Sensitivity of the Fish Inner Ear - Vasconcelos, Raquel O.; Alderks, Peter W.; Sisneros, Joseph A. (Fish Hearing and Bioacoustics: An Anthology in Honor of Arthur N. Popper and Richard R. Fay, 2016)
Fish represent the largest group of vertebrates and display the greatest diversity of auditory structures. However, studies addressing how the form and function of the auditory system change during development to enhance perception of the acoustic environment are rather sparse in this taxon compared to other vertebrate groups. An ontogenetic perspective of the auditory system in fishes provides a readily testable framework for understanding structure–function relationships. Additionally, studying ancestral models such as fish can convey valuable comparable information across vertebrates, as early developmental events are often evolutionary conserved. This chapter reviews the literature on the morphological development of the fish auditory system, with particular focus on the inner ear structures that evolve from an otic placode during early embryonic development and then continue to undergo differentiation and maturation in the postembryonic phase. Moreover, the chapter provides a systematic overview of how auditory sensitivity develops during ontogeny. Although most studies indicate a developmental improvement in auditory sensitivity, there is considerably species-specific variation. Lastly, the paucity of information and literature concerning the development of auditory capabilities for social communication in fishes is also discussed. Further investigation on the development of structure and function of the fish auditory system is recommended in order to obtain a deeper understanding of how ontogenetic morphological changes in the auditory pathway relate to modifications in acoustic reception, auditory processing, and the capacity to communicate acoustically.
Keywords: Auditory development; Auditory physiology; Ear morphology; Fish ontogeny

Fish Sounds and Mate Choice - Amorim, M. Clara P.; Vasconcelos, Raquel O.; Fonseca, Paulo J. (Sound Communication in Fishes, 2015)
Fish acoustic signals associated with mating behaviour are typically low-frequency sounds produced by males when in close proximity to females. However, some species make sounds that serve the function and follow the design of advertisement calls, well known in insects, anurans, and birds. Close-range courtship acoustic signals may be used by females in mate assessment as they contain information of male quality such as size and condition. For example, sound-dominant frequency, amplitude, and fatigue resistance may signal body size whereas pulse period (i.e. muscle contraction rate) and calling activity are related with body condition in some species. Some signal features, such as sound pulse number, may carry multiple messages including size and condition. Playback experiments on mate choice of a restricted number of species suggest that females prefer vocal to silent males and may use sound frequency, amplitude, and mainly calling rateCalling ratewhen assessing males. The assessment of males by females becomes more challenging when males engage in choruses or when sounds are otherwise masked by anthropogenic noise but almost nothing is known about how these aspects affect mating decisions and fish reproductive success.
Keywords: Acoustic communication; Anthropogenic noise; Calling activity; Chorus; Fish; Mate choice; Reproductive success

Hormones and Sexual Behavior of Teleost Fishes - Gonçalves, David; Oliveira, Rui F. (Hormones and Reproduction of Vertebrates, 2011)